Hepatobiliary complications of immune checkpoint inhibitors in cancer - Donna Zhuang; David Zhang; Stephen Riordan (Exploration of Targeted Anti-tumor Therapy, 2024)
Immune checkpoint inhibitors (ICIs) have dramatically changed the landscape of cancer therapy. Over the last decade, both their primary focus in trials and clinical application have exponentially risen, with repeated demonstrations of their efficacy in improving survival in various cancer types. The adverse effects of these drugs on various organ systems were recognised in early phase studies. Given their relatively new emergence on the market, there has been increasing interest into short- and long-term effects and management of ICIs in real-world settings. ICI-related hepatobiliary toxicities are often challenging to diagnose and difficult to distinguish from other causes of deranged liver biochemical tests. The aim of this review is to provide an up-to-date and detailed exploration of the hepatobiliary complications of ICIs, including pathogenesis and approaches to diagnosis and management.